Pluralismo e liberdade no pensamento de Isaiah Berlin - Bachega, Leandro (2017)
The present study aims to follow the British philosopher Isaiah Berlin’s thought (1909-1997) about the history of ideas and, more precisely, in development of his two concepts of liberty: the negative and the positive ones. Searching carefully the XVIII century, Berlin will identify on it the source of several ideologies and political positions current in the twentieth century, putting on risk the individual freedom. In the history of philosophy, Berlin will say, always looking for a definitive truth, to bring the perpetual peace among men, and the full knowledge about them. Berlin will be against this kind of thought, pointing the value pluralism as an incommensurably and incompatibility proof among the several human intents, and the search for a final truth lead the men to an Utopia, with tragic outcome oftentimes